Two mixed valence diruthenium(ii, iii) isomeric complexes show different anticancer properties. Issue 27 (23rd June 2021) - Barresi, Elisabetta; Tolbatov, Iogann; Marzo, Tiziano; Zappelli, Elisa; Marrone, Alessandro; Re, Nazzareno; Pratesi, Alessandro; Martini, Claudia; Taliani, Sabrina; Da Settimo, Federico; La Mendola, Diego
Abstract : Two isomeric Ru2 (ii, iii ) mixed valence compounds show profoundly different anticancer properties due to their activation profiles and their ligands' chemical features. Abstract : In this paper it is demonstrated that the nature of the ligands of two Ru2 (ii, iii ) paddlewheel complexes dramatically affects the overall anticancer properties in cells. Herein, the complex [Ru2 (EB776)4 Cl] was found to be more active against a glioblastoma model with respect to its isomer [Ru2 (EB106)4 Cl]. These different effects depend on the steric hindrance, on the allowed conformations of the complexes and on the presence of hydrophilic regions in [Ru2 (EB776)4 Cl], which overall lead to a lower "steric protection".